Preliminary survey of biofilm forming, antibiotic resistant Escherichia coli in fishes from land based aquaculture systems and open water bodies in Bangladesh - Md. Liton Rana; Md. Ashek Ullah; M. Nazmul Hoque; Jayedul Hassan; Mahbubul Pratik Siddique; Md. Tanvir Rahman (Scientific Reports)
Abstract The emergence and spread of multidrug-resistant pathogens, such as Escherichia coli, present major global public health challenges. This study aimed to investigate the prevalence, antibiotic resistance patterns, biofilm production, and the presence of antibiotic resistance genes (ARGs) and biofilm-forming genes in E. coli isolated from fish in open-body water (wild) sources and land-based aquaculture (cultured) systems in Mymensingh, Bangladesh. We collected 130 fish (Koi: Anabas testudineus and Shing: Heteropneustes fossilis) among which 70 were from wild sources and 60 from cultured systems. We screened 116 probable E. coli isolates through selective culture, Gram-staining, and biochemical tests. Using malB gene-specific PCR, we confirmed 87 isolates (67.0%) as E. coli. Cultured fish had a higher prevalence (70.0%) compared to wild fish (64.0%). Biofilm formation was detected in 20.0% E. coli by Congo red agar tests. However, crystal violet assays revealed that 70.0% of E. coli from cultured fish produced biofilm, compared to 20.0% from wild fish, with 7.0% of cultured fish isolates showing strong biofilm production. Antibiotic resistance profiling showed that 100.0% E. coli isolates were resistant to ampicillin and ceftazidime, beta-lactamase-producing antibiotics. Resistance patterns varied by source, with nearly 97.0% of E. coli from cultured fish being multidrug-resistant (MDR), compared to 60.0% in wild fish. E. coli from cultured fish were identified as potential reservoirs of ARGs such as blaTEM (83.0%), blaSHV (81.0%), blaCTX (78.57%), and the biofilm forming gene fimC (100.0%). Significant associations were observed for blaTEM (p = 0.033), blaSHV (p = 0.038), and fimC (p = 0.005). These findings highlight the need for monitoring β-lactamase-resistant and biofilm-forming E. coli in both wild and cultured fish in Bangladesh due to their potential threat to public health and animal populations.